Constant connectivity and communication stress - Hassan, Arif; Ali, Syed Ahmed (Malaysian Institute of Management, 2017)
The ever-increasing use of electronic and mobile technology has its positive as well as negative consequences. While the technology has improved the work efficiency and performance, it also has diminished the work and personal life boundaries. There is a growing expectation that employees should attend to the messages immediately anytime whether on duty or off duty. Such a work norm may result in communication stress. The paper examines some of these issues in Malaysia through a survey that included 260 employees from a variety of industry, organizations, and job levels who volunteered to participate in the study. The findings indicate that the constant connectivity in terms of frequency (Always or Most of the days) is experienced by more than 50% of the employees, though not all messages were urgent yet almost the same number reported responding to the calls immediately. This possibly has contributed to stress as a significant relationship was found between maintaining constant connectivity with work and communication-related stress. However, no significant outcome in terms of job satisfaction, life satisfaction, work climate, and supervisory behavior was found as a result of after work hour connectivity.